2010
DOI: 10.1016/s0735-1097(10)60864-9
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Reservoir Function Predicts Atrial Fibrillation Recurrence After Catheter Ablation: A Two-Dimensional Speckle Strain Study

Abstract: Background-Predictors of atrial fibrillation (AF) recurrence after catheter ablation (CA) are not fully defined. We hypothesized that 2D left atrial (LA) regional strain maps would help identify abnormal atrial substrate that increases susceptibility to AF recurrence post-CA. Methods and Results-Sixty-three patients (63±10 years, 60% male) underwent CA for symptomatic paroxysmal (75%) or persistent (25%) AF. Baseline LA mechanical function determined using speckle tracking echocardiography was compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
(40 reference statements)
2
32
0
1
Order By: Relevance
“…383,384 New echocardiographic techniques-Two-dimensional speckle-tracking echo has been used as a more sensitive marker to detect early functional remodelling before anatomical alterations occur. [385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400] Strain (S) and strain rate (SR) imaging provide data on myocardial deformation by estimating spatial gradients in myocardial velocities. 385,388,392,393,[401][402][403][404][405] This technique has been used as a surrogate of LA structural remodelling and fibrosis.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…383,384 New echocardiographic techniques-Two-dimensional speckle-tracking echo has been used as a more sensitive marker to detect early functional remodelling before anatomical alterations occur. [385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400] Strain (S) and strain rate (SR) imaging provide data on myocardial deformation by estimating spatial gradients in myocardial velocities. 385,388,392,393,[401][402][403][404][405] This technique has been used as a surrogate of LA structural remodelling and fibrosis.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…388,389,[396][397][398][399][400] Population-based studies have demonstrated the prognostic value of LA strain analysis for long-term outcome. 388,394 Less research and fewer clinical outcomes data are available on the quantification of RA size. Right atrial volumes are also underestimated with 2D echocardiographic techniques compared with 3DE.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%
“…22) Recently, several study groups attempted to clarify the value of LA function to predict AF recurrence using LA deformation imaging in patients undergoing either cardioversion 23,24) or ablation procedures. 8,9,25) In some previous studies, deteriorated LA global strain was suggested to be a risk factor for AF recurrence after ablation. 9,26) LAeF was used in our study and it is a generally accepted representative of LA reservoir function, similar to LA global strain.…”
Section: Discussionmentioning
confidence: 99%
“…2,11-13 With regard to the association between atrial mechanical function and atrial remodeling, atrial mechanical function during sinus rhythm assessed by speckle tracking echocardiography has been shown to be an independent predictor of recurrence of AF or LA reverse remodeling after ablation. 22, 23 Theoretically, the reduced atrial contraction during AF rhythm shown by AFW-V-tvi would predispose to the reduced atrial mechanical function during sinus rhythm. In the present study, AFW-V-tvi correlated well with septal a' velocity during sinus rhythm 1 day after ablation.…”
Section: Patient Characteristics Echocardiographic Variables and Abmentioning
confidence: 99%